Positive electrode slurry and preparation method and application thereof
By grading the particles of the positive electrode active material and dispersing them with the conductive agent first and uniformly, forming a conductive network, the problem of difficult to control the uniformity of the conductive agent is solved, and the conductivity of the positive electrode sheet and the performance of the battery cell are improved.
Patent Information
- Application Number
- CN202411522564.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
The dispersion uniformity of the conductive agent in the existing positive electrode slurry is difficult to control, resulting in unstable battery performance, and commonly used dispersion methods may cause damage to the material or reduce energy density.
By grading the particles of the positive electrode active material, the fine particles and the fine strip-shaped conductive agent are preferentially dispersed uniformly to form an adhesion relationship so that the fibrous and tubular conductive agents and the positive electrode active material particles can better form a conductive network and avoid agglomeration of the conductive agent.
The conductivity of the positive electrode sheet is improved, the stability and uniformity of the slurry are enhanced, the resistance of the diaphragm is reduced, and the performance of the battery cell is improved.
Smart Images

Figure CN119386797A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode slurry and a preparation method and application thereof. Background Art
[0002] With the development of power batteries, in order to ensure the safety, life and performance of batteries, all aspects of battery manufacturing have become more important. Among them, pulping is the starting step in the production process of lithium batteries and is also a key step. It involves the uniform mixing of positive electrode active materials, negative electrode active materials, conductive agents, binders and solvents, and plays a decisive role in battery performance. Generally speaking, the quality of the slurry determines the microstructure of the electrode, which in turn affects the resistance and peeling force of the pole piece, and ultimately affects the internal resistance, rate, cycle life, etc. of the battery cell.
[0003] At present, for some material systems that increase the rate and improve the life, CNT, VGCF and other conductive agents are basically used in the positive electrode slurry. The main function of CNT, VGCF and other conductive agents is to improve the electrical properties, but it is difficult to control the uniformity of their dispersion in the slurry. Commonly used methods include ultrasonic dispersion, high-speed shearing machine, adding dispersants or using ultra-fine grinding beads for electrostatic dispersion. Although these methods can have a certain effect, they will damage the material itself to a certain extent, or introduce non-energy storage materials to reduce the energy density of battery products.
[0004] The particle size of the positive electrode material plays a very important role in the performance of the battery. The narrower the particle size distribution width (diameter distance), the better the material consistency; the compaction can be adjusted by adjusting the diameter distance of the spherical positive electrode material; the smaller the particle size, the more favorable it is for Li + The higher the initial capacity of the material, the higher the internal resistance will be, which will cause safety hazards, increase the irreversible capacity and reduce the cycle performance; at the same time, if it contains oversized particles, it is easy to cause scratches and broken bands during the production process of the pole piece. Therefore, optimizing the strongholds or sites of the conductive agent, binder and positive electrode active material particles in the pole piece and optimizing the preparation process of the positive electrode slurry can optimize compaction, improve uniformity, reduce membrane resistance, and thus improve the performance of the battery cell.
[0005] Based on this, the optimized positive electrode slurry preparation process of the present invention is specially proposed. Summary of the invention
[0006] In view of the defects of the prior art, the purpose of the present invention is to provide a positive electrode slurry and its preparation method and application. The preparation method of the present invention classifies the positive electrode active material particles for slurry preparation in advance, and uniformly disperses the fine particle active material and the thin strip conductive agent particles first, that is, under the condition that the binder is fully dissolved, the fine particle positive electrode active material is preferentially adhered to the fibrous and tubular conductive agent, and the fibrous and tubular conductive agent and the positive electrode active material particles form a better conductive network without changing the original material and its ratio, avoiding the agglomeration of the thin strip conductive agent and improving the conductivity of the positive electrode sheet.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] In a first aspect of the present invention, a method for preparing a positive electrode slurry is provided, wherein the raw materials of the positive electrode slurry include a positive electrode active material, a conductive agent, a binder and a solvent, wherein the conductive agent includes a fibrous and / or tubular conductive agent;
[0009] The preparation method comprises the following steps:
[0010] S1: dividing the initial positive electrode active material raw material into fine particles and coarse particles according to the powder particle size, and the D50 of the fine particles is (0.1-0.5)*D50 of the initial positive electrode active material;
[0011] S2: Mixing a fibrous and / or tubular conductive agent, a binder and an appropriate amount of solvent to obtain a conductive adhesive;
[0012] S3: mixing the fine particles of positive electrode active material obtained in step S1 with the conductive glue obtained in step S2 to obtain an initial slurry A;
[0013] S4: stirring the coarse particles of the positive electrode active material obtained in step S1 with an appropriate amount of solvent to achieve a kneading state, thereby obtaining an initial slurry B;
[0014] S5: Knead and stir the initial slurry A and the initial slurry B, and add a proper amount of solvent to achieve the desired viscosity and solid content, thereby obtaining a positive electrode slurry.
[0015] Furthermore, the positive electrode active material includes at least one of lithium iron phosphate positive electrode material, ternary positive electrode material, and lithium manganese iron phosphate, and the mass proportion of the positive electrode active material in the total powder raw material is 90% to 98%;
[0016] And / or, the fibrous and / or tubular conductive agent is selected from at least one of CNT, VGCF, and MWCNT, and the total mass of the conductive agent accounts for 1% to 8% of the total mass of the powder raw materials;
[0017] And / or, the binder comprises at least one of PVDF and C-PVDF, and the mass proportion of the binder in the total powder raw materials is 1% to 8%;
[0018] And / or, the solvent is NMP, the total amount of which is based on the solid content of the slurry, and the solid content of the positive electrode slurry is in the range of 45% to 65%;
[0019] And / or, the viscosity of the positive electrode slurry is 5000-10000 cps.
[0020] Furthermore, the conductive agent further comprises a point-shaped conductive agent, and the step S4 is replaced by: dry-mixing the coarse-grained positive electrode active material obtained in step S1 with the point-shaped conductive agent, adding an appropriate amount of solvent and continuing to stir to achieve a kneading state after sufficient stirring, to obtain an initial slurry B;
[0021] and / or, K90 of the initial positive electrode active material>1.0, wherein K90=(D90-D10) / D50;
[0022] And / or, the mass percentage of the fine particles in the initial positive electrode active material is 1-15%.
[0023] Further, the point-shaped conductive agent is selected from SP;
[0024] And / or, the K90 of the fine particles is 60% to 95% of the initial positive electrode active material K90.
[0025] Furthermore, in the conductive adhesive in step S2,
[0026] The mass percentage of the fibrous and / or tubular conductive agent in the conductive adhesive is 0.5 to 8%;
[0027] The mass percentage of the binder in the conductive adhesive is 0.1-2%;
[0028] The amount of solvent added is based on the solid content of the conductive adhesive, and the solid content of the conductive adhesive is 1-15%.
[0029] Furthermore, in the preparation process of the conductive adhesive, the appropriate amount of solvent is added in batches;
[0030] And / or, the preparation of the conductive adhesive is completed in a double-layer stirring and guide tube mixing tank;
[0031] And / or, the preparation of the initial slurry A is completed in a double-layer stirring and draft tube mixing tank;
[0032] And / or, the preparation of the initial slurry B is accomplished by using a double planetary high-speed mixer;
[0033] And / or, the kneading and stirring in step S5 is performed in a double planetary high-speed mixer.
[0034] Furthermore, in the preparation process of the conductive adhesive, the adding of the appropriate amount of solvent in batches specifically includes: after the first batch of solvent is added, the solid content of the mixture obtained is 45-55%, after standing for 2-20 minutes, the second batch of solvent is added, and stirring is started when the solid content of the mixture is 25-35%, and then the remaining solvent is added while stirring until the solid content of the mixture is 1-15%, thereby obtaining a conductive adhesive;
[0035] And / or, the solid content of the initial slurry A is 10-30%;
[0036] And / or, in step S3, the stirring speed during the mixing is 20 to 100 rpm;
[0037] And / or, in the double-layer stirring and guide tube mixing tank, a filter is provided on the flow opening located on the side wall of the guide tube, and the flow opening is used for the mutual flow of the material liquid in the main tank and the material liquid in the guide tube, wherein the guide tube is located in the main tank.
[0038] Furthermore, the preparation of the initial slurry B specifically includes: mixing the coarse particles with the dot-shaped conductive agent, setting the double planetary stirring paddle to revolve at 20-50 rpm and rotate at 80-150 rpm, stirring for 8-15 minutes and then stopping; then adding an appropriate amount of NMP, standing for 8-15 minutes and then starting kneading and stirring until a kneading state is reached, and the kneading and stirring conditions are: revolving at 40-70 rpm and rotating at 0 rpm;
[0039] and / or, the solid content of the initial slurry B is 55-75%;
[0040] And / or, the specific method of step S5 includes: adding the initial slurry A to the initial slurry B in the double planetary mixing tank, stirring while adding, and the stirring conditions are: revolution 40-60rpm, rotation 450-550rpm; after the initial slurry A is completely added, the stirring conditions are changed to revolution 40-60rpm, rotation 2500-3500rpm, and continuous stirring for 4-8min, and then the stirring conditions are adjusted to revolution 40-60rpm, rotation 4000-5000rpm, and continuous stirring for 80-100min, then sampling to measure the viscosity and solid content, and controlling the viscosity at 5000-10000cps by solvent, and the stirring conditions during viscosity adjustment are revolution 20-30rpm, rotation 800-1200rpm.
[0041] The second aspect of the present invention provides a positive electrode slurry prepared by the above preparation method.
[0042] According to a third aspect of the present invention, a positive electrode sheet is provided, comprising a current collector and a positive electrode active material layer disposed on the surface of the current collector, wherein the positive electrode active material layer is formed by coating the positive electrode slurry prepared by the above method on the current collector.
[0043] The method for preparing the positive electrode slurry provided by the present invention, the positive electrode slurry prepared by the method and their applications have the following beneficial effects:
[0044] 1. The positive electrode active material particles for slurry preparation are pre-sized according to specific requirements and divided into fine particles and coarse particles. Then, the fine particles and thin strip-shaped conductive agent particles are uniformly dispersed first, that is, the fine particles of positive electrode active material are preferentially adhered to the fibrous and tubular conductive agents under the condition that the binder is fully dissolved. Without changing the original material and its ratio, the fibrous and tubular conductive agents and the positive electrode active material particles form a better conductive network, thereby improving the conductivity of the positive electrode sheet.
[0045] 2. The present invention first prepares a slurry of fibrous and tubular conductive agents and a binder, and then adds fine particles of positive electrode active material after the conductive agent is evenly dispersed in the slurry to form a conductive glue. Subsequently, the fine particles are stirred to form adhesion with the fibrous and tubular conductive agents first, which can not only improve the stability and uniformity of the slurry, but also better form a conductive network.
[0046] 3. When preparing the conductive adhesive and the initial slurry A, a double-layer stirring guide tube mixing tank is preferably used to improve the uniformity of the slurry mixing. A guide tube mixing tank with a filter is preferably used as an auxiliary to improve the stirring and dispersing ability while weakening the stirring shear strength, thereby reducing damage to fibrous and tubular materials.
[0047] 4. In the preferred preparation scheme of the conductive adhesive of the present invention, PVDF is fully dissolved during the capillary absorption process of the thin strip conductive agent and the damage to the material caused by stirring at a high solid content is avoided. Then, stirring is started at a lower solid content, thereby reducing shear damage and power consumption.
[0048] 5. The present invention performs particle size classification on the positive electrode active material, and the obtained fine powder is first mixed with tubular, fibrous and other conductive agents. These tubular and fibrous conductive agents are materials with large aspect ratios, and are easy to bend and agglomerate into balls during stirring. The actual density of the extremely small positive electrode active material fine powder is greater than that of the conductive agent, and it is easy to adsorb on the conductive agent to play a pinning and strengthening role, so that the original agglomerated conductive agent is unzipped and dispersed; although it is difficult for the fine powder to maintain the adsorption state during stirring, its own inertia is large and can play a buffering and moving effect, that is, it plays the role of a windbreak, making it difficult for the conductive agent to agglomerate. If the positive electrode active material mixed with the conductive agent also includes coarse particles, that is, when coarse and fine particles are mixed with the conductive agent together, the coarse particles are too large inertia, and it is easy to group the conductive agent, that is, the conductive agent is easy to self-agglomerate, and ultimately the fine particles cannot be covered by the conductive agent network, and the best dispersion effect cannot be achieved. Therefore, the present invention classifies the initial positive electrode active material and mixes the fine particles with the tubular, fibrous, etc. conductive agent first, which can prevent the conductive agent component from agglomerating into balls and also prevent the fine powder positive electrode active material from agglomerating.
[0049] 6. In the preferred embodiment of the present invention, a guide tube mixing tank is used to prepare the conductive adhesive, and a filter screen in the guide tube is used for convection dispersion. The filter screen plays a role in breaking up and cutting agglomerates, and also increases the local flow velocity of the guide port to prevent stirring into balls;
[0050] 7. The preferred A and B tanks of the guide tube mixing tank of the present invention are used for pulping and mixing at the same time to meet the dispersion requirements of different components, reduce the dispersion difficulty of thin strip raw materials such as carbon nanotubes, and improve pulping efficiency.
[0051] 8. The positive electrode slurry prepared by the method of the present invention has high uniformity and stability, and the positive electrode sheet prepared by coating the positive electrode slurry has low film resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0053] Figure 1 A flow chart for preparing positive electrode slurry according to an embodiment of the present invention. DETAILED DESCRIPTION
[0054] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0055] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0056] A first aspect of the present invention provides a method for preparing a positive electrode slurry, wherein the raw materials of the positive electrode slurry include a positive electrode active material, a conductive agent, a binder and a solvent, wherein the conductive agent includes a fibrous and / or tubular conductive agent;
[0057] The preparation method comprises the following steps:
[0058] S1: dividing the initial positive electrode active material raw material into fine particles and coarse particles according to the powder particle size, and the D50 of the fine particles is (0.1-0.5)*D50 of the initial positive electrode active material;
[0059] S2: Mixing a fibrous and / or tubular conductive agent, a binder and an appropriate amount of solvent to obtain a conductive adhesive;
[0060] S3: mixing the fine particles of positive electrode active material obtained in step S1 with the conductive glue obtained in step S2 to obtain an initial slurry A;
[0061] S4: stirring the coarse particles of the positive electrode active material obtained in step S1 with an appropriate amount of solvent until they are close to a kneading state, thereby obtaining an initial slurry B;
[0062] S5: Knead and stir the initial slurry A and the initial slurry B, and add a proper amount of solvent to achieve the desired viscosity and solid content, thereby obtaining a positive electrode slurry.
[0063] The D50 of the fine particles in step S1 is (0.1-0.5)*D50 of the initial positive electrode active material, for example: the D50 of the fine particles is 0.15*D50 of the initial positive electrode active material, the D50 of the fine particles is 0.2*D50 of the initial positive electrode active material, the D50 of the fine particles is 0.3*D50 of the initial positive electrode active material, the D50 of the fine particles is 0.4*D50 of the initial positive electrode active material, and the D50 of the fine particles is 0.5*D50 of the initial positive electrode active material. If the D50 of the fine particles in step S1 is too large, it means that some of the fine particles are coarser, which will affect the uniform dispersion of the fibrous and / or tubular conductive agent, and the pinning strengthening effect of the fine particles on the conductive agent is weak, causing some of the conductive agents to agglomerate; and if the D50 of the fine particles is too small, the number of fine particles is too small, the pinning strengthening effect will also be weakened, which is not conducive to the uniform dispersion of the conductive agent.
[0064] The preparation method of the positive electrode slurry of the present invention is to optimize the preparation method of the conventional positive electrode slurry to obtain a slurry that is uniformly mixed and stable. Even if the conductive agent is a fibrous or tubular material, its dispersion can be well controlled to reduce the agglomeration of the conductive agent, and the agglomeration of fine powder particles into balls is reduced, thereby improving the conductivity of the positive electrode sheet obtained therefrom. The preparation method of the present invention is to pre-size the positive electrode active material particles for slurry preparation according to specific requirements, and divide them into fine particles and coarse particles; when preparing the conductive glue, only the fibrous and tubular conductive agents and the binder are mixed, so that the outer periphery of the thin strip conductive agent is uniformly attached to the dissolved glue, and the positive electrode active material fine particles are added after the conductive agent of this type is uniformly dispersed in the glue to form a conductive glue, and then the fine particles are preferentially adhered to the fibrous and tubular conductive agents by stirring, so as to play a pinning role on the thin strip conductive agent to avoid its agglomeration, thereby obtaining the initial slurry A, which is not only conducive to improving the stability and uniformity of the slurry, but also can better form a conductive network to avoid the agglomeration of the fine particles of the active material.
[0065] For the coarse particles of positive electrode active material, if the conductive agent includes point-shaped or granular conductive agents in addition to fibrous and tubular conductive agents, the coarse particles of active material alone and the point-shaped conductive agent are mixed with an appropriate amount of solvent to form an initial slurry B, and finally the initial slurry A and the initial slurry B are mixed to obtain the final positive electrode slurry; if the conductive agent does not include conductive agents other than fibrous and tubular conductive agents, the coarse particles of positive electrode active material are directly mixed with an appropriate amount of solvent to form initial slurry B.
[0066] As a preferred embodiment, the conductive agent also includes a point-shaped conductive agent. In this case, the step S4 is replaced by: dry-mixing the coarse-grained positive electrode active material obtained in step S1 with the point-shaped conductive agent, adding an appropriate amount of solvent and continuing to stir to make it reach a kneading state after sufficient stirring, to obtain an initial slurry B. Further, the mass ratio of the fibrous and / or tubular conductive agent to the point-shaped conductive agent is not limited. Typically, the mass ratio of the fibrous and / or tubular conductive agent to the point-shaped conductive agent is 1:0.05 to 10 (for example, 1:0.10, 1:0.50, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9). For the present invention, when the total amount of the conductive agent remains unchanged, the more the point-shaped conductive agent, the less the corresponding long strip-shaped conductive agent. The more the proportion of the point-shaped conductive agent is, the more suitable it is for the positive electrode active material with a relatively concentrated diameter, and the size of such positive electrode particles is close; the mixing of the point-shaped conductive agent and the coarse particles can also play a good advantage.
[0067] The positive electrode active material can be a positive electrode active material commonly used in the field of secondary battery manufacturing, typically including but not limited to at least one of lithium iron phosphate positive electrode material (LFP), ternary positive electrode material (NCM), and lithium iron manganese phosphate (LMFP). The mass proportion of the positive electrode active material in all powder raw materials is preferably 90% to 98% (for example, 91%, 92%, 93%, 94%, 95%, 96%, 97%); all powder raw materials include positive electrode active materials, conductive agents and binders.
[0068] The conductive agent can be a conductive agent commonly used in the field of secondary battery manufacturing, typically including but not limited to at least one of fibrous and / or tubular conductive agents CNT (carbon nanotubes), VGCF (carbon nanofibers), MWCNT (multi-walled carbon nanotubes) and optional point-shaped conductive agents SP (carbon black). The total mass of the conductive agent preferably accounts for 1% to 8% (for example, 2%, 3%, 4%, 5%, 6%, 7%) of the total mass of the powder raw materials; all powder raw materials include positive electrode active materials, conductive agents and binders.
[0069] The binder can be a binder commonly used in the field of secondary battery manufacturing, typically including but not limited to at least one of polyvinylidene fluoride (PVDF) and carboxylated polyvinylidene fluoride (C-PVDF). The mass proportion of the binder in all powder raw materials is preferably 1% to 8% (for example, 2%, 3%, 4%, 5%, 6%, 7%); all powder raw materials include positive electrode active materials, conductive agents and binders.
[0070] The solvent can be a positive electrode slurry solvent commonly used in the field of secondary battery manufacturing. Typically, but not limitedly, the solvent is NMP, and the total amount added is based on the solid content of the positive electrode slurry. The solid content range of the positive electrode slurry is preferably 45% to 65% (for example, 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%).
[0071] The viscosity of the positive electrode slurry is not limited and can be a conventional viscosity. As an optional manner, the viscosity of the positive electrode slurry is 5000 to 10000 cps (eg, 6000 cps, 7000 cps, 8000 cps, 9000 cps).
[0072] The solid content determination methods mentioned in the present invention are all conventional determination methods in the art, such as the drying loss method or the oven drying method.
[0073] The initial positive electrode active material used in the preparation method of the present invention can be any commercially available positive electrode active material, and there is no particular restriction on its particle size range. Typically, the particle size D50 of the lithium iron phosphate positive electrode material is 0.5 to 10 microns (such as 1 micron, 3 microns, 6 microns, 9 microns), the particle size D50 of the nickel-cobalt-manganese ternary positive electrode material is 1.5 to 20 microns (such as 2 microns, 4 microns, 6 microns, 8 microns, 10 microns, 12 microns, 14 microns, 16 microns, 18 microns), and the particle size D50 of the lithium iron manganese phosphate is 0.5 to 5 microns (such as 1 micron, 2 microns, 3 microns, 4 microns). However, in order to ensure the number of fine particles, it is preferred that the K90 of the initial positive electrode active material is greater than 1.0 (such as K90 is 1.2, 1.5, 2, 2.5, 3, etc.), wherein K90 = (D90-D10) / D50;
[0074] In order to ensure the quantity of fine particles and better build a conductive network, the mass percentage of the fine particles in the initial positive electrode active material is 1-15% (such as 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%). The fine particles should not be too many or too few. Too few fine particles cannot achieve the pinning effect and the improvement of conductivity is limited. Too many fine particles are easy to agglomerate.
[0075] The K90 of the fine particles is less than the K90 of the original powder, so as to ensure that there are no coarse particles in the fine particles; preferably, the K90 of the fine particles is 60% to 95% (such as 70%, 80%, 90%) of the initial positive electrode active material K90.
[0076] In order to obtain the required mass of fine-particle positive active material from the initial positive active material, a dry inertial classification device or a simple vibrating screen can be used to obtain graded fine particles by adjusting the airflow size or the mesh size of the screen. The D50 of the fine particles used for the initial slurry A is (0.1-0.5)*the D50 of the initial positive active material. If the required weight of fine particle powder cannot be obtained by screening or grading once, a second screening or even more screenings can be performed. For example, if the weight of the fine powder screened out for the first time is lower than the weight required for step S3, the fine powder can be further screened out from the remaining coarse powder, and then the fine powders obtained after multiple screenings are combined to form all the fine particles required for step S3 of the present invention. Of course, if the fine particles screened out for the second time and the fine particles screened out for the first time are added together to exceed all the fine particles required for step S3, the remaining amount of fine particles can be screened out from the fine particles screened out for the second time.
[0077] The conductive glue in step S2 should include all the fibrous and / or tubular conductive agents and binders required for preparing the positive electrode slurry. Preferably, the mass percentage of the binder in the conductive glue is 0.1-2%, which is more conducive to the subsequent step S3.
[0078] Further, the mass percentage of the fibrous and / or tubular conductive agent in the conductive adhesive of step S2 is 0.5-8% (e.g., 1%, 2%, 3%, 4%, 5%, 6%, 7%);
[0079] Furthermore, the amount of the solvent added in step S2 is based on the solid content of the conductive adhesive, and the solid content of the conductive adhesive is 1-15% (eg, 2%, 6%, 8%, 10%, 12%, 14%).
[0080] In order to avoid the damage of the thin strip conductive agent and other materials by stirring at high solid content, in the preparation process of the conductive glue, the appropriate amount of solvent is added in batches; preferably, in the preparation process of the conductive glue, the appropriate amount of solvent is added in batches specifically including: the solid content of the mixture obtained after the first batch of solvent is added is 45-55% (such as 48%, 50%, 52%), after standing for 2-20 minutes (such as 6 minutes, 9 minutes, 12 minutes, 15 minutes, 18 minutes), and then the second batch of solvent is added, and the solid content of the mixture is 25-35% (such as 28%, 30%, 32%, 34%). Stirring begins, and then the remaining solvent is added while stirring until the solid content in the mixture is 1-15%, thereby obtaining the conductive glue. First, a small amount of solvent is added and kept standing, so that the PVDF can be fully dissolved during the capillary absorption of the thin strip conductive agent and the damage of the material by stirring at high solid content can be avoided, and then stirring is started at a lower solid content, which reduces shear damage and power consumption.
[0081] The mixing treatment involved in the preparation method of the present invention can adopt conventional mixing equipment for slurry preparation. As a preferred embodiment, the preparation of the conductive adhesive is completed in a double-layer stirring guide tube mixing tank; the preparation of the initial slurry A is completed in a double-layer stirring guide tube mixing tank; the preparation of the initial slurry B is completed by using a double planetary high-speed mixer; the kneading and stirring in step S5 is completed in a double planetary high-speed mixer.
[0082] The double-layer stirring guide tube mixing tank involved in the present invention can be any conventional double-layer mixing tank with inner and outer outer configurations, and the inner tube and the outer tank body can form exchange, diversion or convection of liquid. Typically, but not limitedly, the specific structure of the double-layer stirring guide tube mixing tank can be found in patent CN220048129U. The double-layer guide tube stirring tank used in the specific embodiment of the present invention is based on the device recorded in patent CN220048129U, wherein there are only two guide windows, and the windows are completely covered by an 80-mesh filter screen, the window width is 1 / 8 of the circumference of the guide tube, the window height is 1 / 2 of the height of the guide tube, the lowest point of the window is on the center line of the guide tube, that is, the uppermost opening, the liquid inlet pipe and the feeding port are both arranged on the guide tube cover plate, the upper layer is a folding blade stirring paddle, and the lower layer is a curved blade turbine type, the height-to-diameter ratio of the mixing tank is 2:1, the diameter ratio of the guide tube to the main tank is 2:3, and the height ratio of the guide tube to the main tank is 3:4. When using this equipment, the total volume of the slurry is controlled at about 80% of the tank volume to ensure slurry convection inside and outside the guide window.
[0083] In the double-layer stirring and guiding tube mixing tank, a filter screen is preferably provided on the flow opening on the side wall of the guiding tube, and the flow opening is used for the mutual flow of the material liquid in the main tank and the material liquid in the guiding tube, wherein the guiding tube is located in the main tank (i.e., the kettle body). The filter screen is preferably an 80-mesh filter screen.
[0084] When preparing the conductive adhesive and the initial slurry A, a double-layer stirring guide tube mixing tank is preferably used to improve the uniformity of slurry mixing. Preferably, a guide tube mixing tank with a filter is used as an auxiliary to improve the stirring and dispersing ability and reduce the damage to fibrous and tubular materials by weakening the stirring shear strength. In the preferred embodiment of the present invention, a guide tube mixing tank is used to prepare the conductive adhesive, and the filter screen in the guide tube is used for convection dispersion. The filter screen plays the role of breaking up and dividing the agglomerates, and also plays the role of increasing the local flow rate of the guide port. The 80-mesh filter screen can play the above role and effectively prevent blockage and prevent stirring into balls. In order to ensure the mixing effect of the slurry, the solid content of the initial slurry A is preferably 10-30% (such as 15%, 20%, 25%).
[0085] In step S3, the stirring speed during the mixing is preferably 20 to 100 rpm (such as 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, 90 rpm).
[0086] The preparation of the initial slurry B can be mixed by a conventional method. Preferably, the preparation of the initial slurry B specifically includes: mixing the coarse particles with the point-shaped conductive agent, setting a double planetary stirring paddle to revolve at 20 to 50 rpm (for example, 30 rpm, 40 rpm) and rotate at 80 to 150 rpm (for example, 90 rpm, 100 rpm, 110 rpm, 120 rpm, 130 rpm, 140 rpm), and stirring for 8 to 15 minutes (for example, 10 minutes, 12 minutes, 14 minutes) and then stopping; then adding an appropriate amount of NMP, standing for 8 to 15 minutes (for example, 10 minutes, 12 minutes, 14 minutes), and then starting kneading and stirring until it reaches a kneading state. The conditions of the kneading and stirring are: revolving at 40 to 70 rpm (for example, 50 rpm, 60 rpm) and rotating at 0 rpm;
[0087] The initial slurry B can also be controlled by solid content, and the solid content of the initial slurry B is preferably 55-75% (e.g., 60%, 65%, 70%);
[0088] In order to make the mixing more uniform and the obtained slurry more stable, preferably, the specific method of step S5 includes: adding the initial slurry A to the initial slurry B in the double planetary stirring tank, stirring while adding, and the stirring conditions are: revolution 40-60rpm (for example, 50rpm), rotation 450-550rpm (for example, 500rpm); after the initial slurry A is completely added, the stirring conditions are changed to revolution 40-60rpm (for example, 50rpm), rotation 2500-3500rpm (for example, 3000rpm), and stirring is continued for 4-8min (for example, 5min, 6min, 7min), and then the stirring conditions are adjusted to revolution 40-60rpm (for example, 50rpm), rotation 2500-3500rpm (for example, 3000rpm), and stirring is continued for 4-8min (for example, 5min, 6min, 7min). The mixture is stirred for 80 to 100 minutes (e.g. 85 minutes, 90 minutes, 95 minutes), and then samples are taken to measure the viscosity and solid content, and the viscosity is controlled at 5000 to 10000 cps (e.g. 6000 cps, 7000 cps, 8000 cps, 9000 cps) by using a solvent. The stirring conditions during the viscosity adjustment period are revolution of 20 to 30 rpm (e.g. 25 rpm) and rotation of 800 to 1200 rpm (e.g. 900 rpm, 1000 rpm, 1100 rpm).
[0089] The second aspect of the present invention provides a positive electrode slurry prepared by the method of the first aspect. The positive electrode slurry is uniform and has stable viscosity. After 24 hours, the slurry viscosity does not change much, less than 3% (such as 2.5%, 2.0%, 1.5%, 1.0%, 0.5%).
[0090] The third aspect of the present invention also provides a positive electrode sheet, including a current collector and a positive electrode active material layer arranged on the surface of the current collector, wherein the positive electrode active material layer is formed by coating the positive electrode slurry prepared by the method described in the first aspect on the current collector.
[0091] The positive electrode slurry of the present invention can be applied to the preparation of secondary batteries, especially lithium batteries.
[0092] The diaphragm resistance is tested using a pole piece resistance meter, with a set pressure of 25 MPa and a pressure maintenance of 15 seconds.
[0093] The present invention is further described in detail below in conjunction with specific embodiments and comparative examples, but the examples do not limit the present invention in any form. The size specifications of the CNT used in the following embodiments and comparative examples are: tube diameter 1.5-60nm, aspect ratio: 50-10000:1; the size specifications of the VGCF are: tube diameter 150nm, aspect ratio: 50-5000:1; the particle size of the SP is 10-100nm.
[0094] Example 1 (Pulping formula: LFP:CNT:SP:PVDF=97:1:0.5:1.5)
[0095] (1) According to the pulping formula, the positive electrode active particles (D50 = 1.5 μm, K90 = 3.0) required for pulping are divided into 97 parts, and the weight is recorded as 97 m. The positive electrode active particles are subjected to particle size classification in a dry inertial classification device. The classification is stopped when the weight of the fine particles obtained after multiple classifications reaches 2 m. The D50 of the fine particles is 0.35 μm, and K90 is 1.8.
[0096] (2) All the remaining coarse particles (95 m) collected in step (1) were mixed with 0.5 m SP, and the double planetary stirring paddles were set to revolve at 30 rpm and rotate at 100 rpm for 10 min and then stopped; then NMP was added and the weight of NMP reached 50 m, and then it was allowed to stand for 10 min; kneading and stirring were started, with the revolution at 50 rpm and the rotation at 0 rpm; when a semi-dry uniform mud effect was achieved (i.e., near the kneading state), the initial slurry B was completed, and the slurry solid content reached 65%.
[0097] (3) Weigh 1mCNT and 1.5mPVDF, put them all into the guide tube stirring tank, then add NMP until the solid content is 50%, stop adding, let it stand for 5 minutes for capillary absorption, and then continue to add NMP until the solid content is 30%, start stirring, and the stirring rate is 20rpm. At this stage, add NMP while stirring, and stop adding when the solid content reaches 14.3%. At this time, the conductive glue is obtained. After continuing to stir for 5 minutes, add 2m of fine particles obtained by classification in step (1) from the feed port of the guide tube stirring tank, adjust the speed to 30rpm, and after stirring for 30 minutes, observe the agglomeration situation through a microscope in real time. When no agglomeration occurs when adjusting multiple fields of view, it means that the initial slurry A is successfully prepared. At this time, the slurry solid content reaches 23%.
[0098] (4) The prepared initial slurry A is released from the bottom valve of the guide tube stirring tank into the double planetary stirring tank, and stirring is started while adding, with a revolution of 50 rpm and a rotation of 500 rpm. After all the initial slurry A is added, the stirring is changed to a revolution of 50 rpm and a rotation of 3000 rpm for 5 minutes, and then changed to a revolution of 50 rpm and a rotation of 4500 rpm for 90 minutes. Sampling is started to measure the viscosity and solid content, and the guide tube stirring tank is rinsed with NMP to obtain the regeneration liquid. The regeneration liquid is used to adjust the viscosity so that the viscosity is controlled at 5000-10000 cps. During the viscosity adjustment period, the revolution is 25 rpm and the rotation is 1000 rpm. At this point, a slurry with a solid content of 59% and an initial viscosity of 8490 cps is obtained, and stirring is continued at the end point. After 24 hours, the slurry viscosity increases by 3%.
[0099] The positive electrode slurry obtained in this embodiment is prepared at 380 g / m 2 The double-sided surface density is coated on aluminum foil at 2.6g / cm 3 The compaction density was roller pressed, and the final electrode sheet had a diaphragm resistance of 36mΩ.
[0100] Example 2: (Pulping formula: LFP:CNT / VGCF:SP:PVDF=90:6:0.5:3.5)
[0101] (1) According to the slurry formula, the positive electrode active particles (D50 = 0.83 μm, K90 = 2.2) required for slurry are divided into 90 portions, and the weight is recorded as 90 m. The positive electrode active particles are subjected to particle size classification in a dry inertial classification device. After the weight of the fine particles obtained after multiple classifications reaches 5 m, the classification is stopped. The D50 of the fine particles is 0.27 μm, and K90 is 1.6;
[0102] (2) All the remaining coarse particles (85 m) collected in step (1) were mixed with 0.5 m SP, and the double planetary stirring paddles were set to revolve at 20 rpm and rotate at 50 rpm for 10 min and then stopped; then NMP was added and the weight reached 60 m, and then the mixture was allowed to stand for 20 min; kneading and stirring were started, with the revolution at 50 rpm and the rotation at 0 rpm; when a semi-dry uniform mud effect was achieved, the initial slurry B was completed, and the slurry solid content reached 59%.
[0103] (3) Weigh 2.5mCNT, 3.5mVGCF and 3.5mPVDF, and put them all into the guide tube stirring tank, then add NMP until the solid content is 50%, stop adding, let it stand for 5 minutes for capillary absorption, and then continue to add NMP until the solid content is 30%, start stirring, and the stirring rate is 20rpm. At this stage, add NMP while stirring, and stop adding when the solid content is 13.6%. At this time, the conductive glue is obtained. After continuing to stir for 5 minutes, add 5m of fine particles obtained by classification in step (1) from the feed port of the guide tube stirring tank, adjust the speed to 30rpm, and observe the agglomeration situation through a microscope after stirring for 30 minutes. When no agglomeration occurs when adjusting multiple fields of view, it means that the initial slurry A is successfully prepared. At this time, the slurry solid content reaches 19.5%.
[0104] (4) The prepared initial slurry A is released from the bottom valve of the guide tube stirring tank into the double planetary stirring tank, and stirring is started while adding, with a revolution of 50 rpm and a rotation of 500 rpm. After all the initial slurry A is added, the stirring is changed to a revolution of 50 rpm and a rotation of 3000 rpm for 5 minutes, and then changed to a revolution of 50 rpm and a rotation of 4500 rpm for 60 minutes. Sampling is started to measure the viscosity and solid content, and the guide tube stirring tank is rinsed with NMP to obtain the regeneration liquid. The regeneration liquid is used to adjust the viscosity so that the viscosity is controlled at 5000-10000 cps. During the viscosity adjustment period, the revolution is 25 rpm and the rotation is 1000 rpm. At this point, a slurry with a solid content of 45% and an initial viscosity of 7342 cps is obtained, and stirring is continued at the end point. After 24 hours, the slurry viscosity increases by 0.8%.
[0105] The positive electrode slurry obtained in this embodiment is prepared at 240 g / m 2 The double-sided surface density is coated on aluminum foil at 2.5g / cm 3 The compaction density was roller pressed, and the final electrode sheet had a diaphragm resistance of 8mΩ.
[0106] Example 3: (Pulping formula: NCM111: CNT: SP: PVDF = 92: 3: 1.5: 3.5)
[0107] (1) According to the pulping formula, the positive electrode active particles (D50 = 12.5 μm, K90 = 1.3) required for pulping are divided into 92 parts, and the weight is recorded as 92 m. The positive electrode active particles are subjected to particle size classification in a dry inertial classification device. The classification is stopped when the weight of the fine particles obtained after multiple classifications reaches 12 m. The D50 of the fine particles is 2.3 μm, and K90 is 0.8.
[0108] (2) All the remaining coarse particles (80 m) collected in step (1) were mixed with 1.5 m SP, and the double planetary agitator was set to revolve at 30 rpm and rotate at 500 rpm for 15 min and then stopped; then NMP was added and the weight reached 40 m, and then the mixture was allowed to stand for 10 min; kneading and stirring were started, with the revolution at 50 rpm and the rotation at 0 rpm; when a semi-dry uniform muddy effect was achieved, the initial slurry B was completed, and the solid content of the slurry reached 67%.
[0109] (3) Weigh 3mCNT and 3.5mPVDF, put them all into the guide tube stirring tank, then add NMP until the solid content is 50%, stop adding, let it stand for 5 minutes for capillary absorption, and then continue to add NMP until the solid content is 30%, start stirring, and the stirring rate is 20rpm. At this stage, add NMP while stirring, and stop adding when the solid content reaches 11.5%. At this time, the conductive glue is obtained. After continuing to stir for 5 minutes, add 12m of fine particles obtained by classification in step (1) from the feed port of the guide tube stirring tank, adjust the speed to 30rpm, and after stirring for 60 minutes, observe the agglomeration situation through a microscope in real time. When no agglomeration occurs when adjusting multiple fields of view, it means that the initial slurry A is successfully prepared. At this time, the slurry solid content reaches 27%.
[0110] (4) The prepared initial slurry A is released from the bottom valve of the guide tube stirring tank into the double planetary stirring tank, and stirring is started while adding, with a revolution of 50 rpm and a rotation of 500 rpm. After all the initial slurry A is added, the stirring is changed to a revolution of 50 rpm and a rotation of 3000 rpm for 5 minutes, and then changed to a revolution of 50 rpm and a rotation of 4500 rpm for 90 minutes. Sampling is started to measure the viscosity and solid content, and the guide tube stirring tank is rinsed with NMP to obtain the regeneration liquid. The regeneration liquid is used to adjust the viscosity so that the viscosity is controlled at 5000-10000 cps. During the viscosity adjustment period, the revolution is 20 rpm and the rotation is 1000 rpm. At this point, a slurry with a solid content of 51% and an initial viscosity of 5370 cps is obtained, and stirring is continued at the end point. After 24 hours, the slurry viscosity increases by 2.3%.
[0111] The positive electrode slurry obtained in this embodiment is prepared at 450 g / m 2 The double-sided surface density is coated on aluminum foil at 3.5g / cm 3The compaction density was roller pressed, and the final electrode sheet had a diaphragm resistance of 23mΩ.
[0112] Embodiment 4:
[0113] The pulping formula of this embodiment is: LMFP / NCM523:CNT / VGCF:SP:PVDF=94:3:0.5:2.5
[0114] (1) According to the pulping formula, the positive electrode active particles (D50 = 8.6 μm, K90 = 1.8) required for pulping are divided into 94 parts, and the weight is recorded as 94 m, wherein the mass ratio of LMFP to NCM523 is 8:2. The positive electrode active particles are subjected to particle size classification in a dry inertial classification device, and the classification is stopped after the weight of the fine particles obtained after multiple classifications reaches 8 m, and the D50 of the fine particles is 2.8 μm, and K90 is 0.9.
[0115] (2) Mix all the remaining coarse particles (86 m) collected in step (1) with 0.5 m SP, set the double planetary agitator to revolve at 30 rpm and rotate at 100 rpm, and stop after 10 min; then add NMP and let the weight reach 50 m, let it stand for 10 min; start kneading and stirring, revolve at 50 rpm and rotate at 0 rpm; when a semi-dry uniform mud effect is achieved, it means that the initial slurry B is completed, and the slurry solid content reaches 74%.
[0116] (3) Weigh 3mCNT / VGCF (where the mass ratio of CNT to VGCF is 1:1) and 2.5mPVDF, put them all into the guide tube stirring tank, and then add NMP until the solid content reaches 50%, stop adding, let it stand for 5 minutes for capillary absorption, and then continue to add NMP until the solid content reaches 30%, start stirring, and the stirring rate is 20rpm. At this stage, add NMP while stirring, and stop adding when the solid content reaches 4.8%. At this time, the conductive glue is obtained. After continuing to stir for 5 minutes, add 8m of fine particles obtained by classification in step (1) from the feed port of the guide tube stirring tank, adjust the speed to 30rpm, and observe the agglomeration situation through a microscope after stirring for 30 minutes. When no agglomeration occurs when adjusting multiple fields of view, it means that the initial slurry A is successfully prepared. At this time, the slurry solid content reaches 11%.
[0117] (4) The prepared initial slurry A is released from the bottom valve of the guide tube stirring tank into the double planetary stirring tank, and stirring is started while adding, with a revolution of 50 rpm and a rotation of 500 rpm. After all the initial slurry A is added, the stirring is changed to a revolution of 50 rpm and a rotation of 3000 rpm for 5 minutes, and then changed to a revolution of 50 rpm and a rotation of 4500 rpm for 90 minutes. Sampling is started to measure the viscosity and solid content, and the guide tube stirring tank is rinsed with NMP to obtain the regeneration liquid. The regeneration liquid is used to adjust the viscosity so that the viscosity is controlled at 5000-10000 cps. During the viscosity adjustment period, the revolution is 25 rpm and the rotation is 1000 rpm. At this point, a slurry with a solid content of 41% and an initial viscosity of 6890 cps is obtained, and stirring is continued at the end point. After 24 hours, the slurry viscosity increases by 2.3%.
[0118] The positive electrode slurry obtained in this embodiment was prepared at a pressure of 200 g / m 2 The double-sided surface density is coated on aluminum foil at 2.9g / cm 3 The compaction density was roller pressed, and the final electrode sheet had a diaphragm resistance of 38mΩ.
[0119] Comparative Example 1: (Pulping formula: LFP:CNT:SP:PVDF=97:1:0.5:1.5)
[0120] According to the slurry formula, the positive active particles required for slurrying are divided into 97 parts, and the weight is recorded as 97m. Weigh 1.5m of PVDF and place it in a double planetary stirring tank, add 65m of NMP, and after standing for 10min, set the double planetary stirring paddle to revolve at 10rpm and rotate at 1000rpm and start stirring. Stop after 90min to obtain the glue. Mix LFP, CNT and SP and add them to the glue, start stirring, revolve at 50rpm and rotate at 100rpm. After 10min, adjust the speed, revolve at 50rpm and rotate at 4500rpm. After 90min, start sampling to measure the viscosity and solid content. Add NMP to adjust the viscosity so that the viscosity is controlled at 5000-10000cps. During the viscosity adjustment period, revolve at 25rpm and rotate at 1000rpm. At this point, a slurry with a solid content of 59% and an initial viscosity of 5530cps is obtained, and stirring is continued at the end point. After 24h, the viscosity of the slurry increases by 23%.
[0121] The positive electrode slurry obtained in this comparative example was prepared at 380 g / m 2 The double-sided surface density is coated on aluminum foil at 2.6g / cm 3 The compaction density was roller pressed, and the final electrode sheet had a diaphragm resistance of 152mΩ.
[0122] Comparative Example 2 (Pulping formula: LFP:CNT:SP:PVDF=97:1:0.5:1.5)
[0123] This comparative example omits the classification process of the positive electrode active material on the basis of Example 1, and the specific operation steps are as follows:
[0124] (1) The positive electrode active particles (D50 = 1.5 μm, K90 = 3.0) (97 m) to be slurried are mixed with 0.5 m SP, and the double planetary stirring paddles are set to revolve at 30 rpm and rotate at 100 rpm for 10 min and then stopped; then NMP is added and the weight of NMP reaches 50 m, and then it is allowed to stand for 10 min; kneading and stirring are started, with the revolution at 50 rpm and the rotation at 0 rpm; when a semi-dry uniform mud effect is achieved (i.e., near the kneading state), the initial slurry B is completed, and the solid content of the slurry reaches 66.1%.
[0125] (2) Weigh 1 mCNT and 1.5 mPVDF, put them all into a flow tube stirring tank, and then add NMP until the solid content reaches 50%, stop adding, let it stand for 5 minutes for capillary absorption, and then continue to add NMP until the solid content reaches 30%, start stirring, and the stirring rate is 20 rpm. At this stage, add NMP while stirring, and stop adding when the solid content reaches 14.3%. At this time, a conductive adhesive solution is obtained.
[0126] (3) The prepared conductive glue is released from the bottom valve of the guide tube stirring tank into the double planetary stirring tank, and stirring is started while adding, with a revolution of 50 rpm and a rotation of 500 rpm. After all the conductive glue is added, the stirring is changed to a revolution of 50 rpm and a rotation of 3000 rpm for 5 minutes, and then changed to a revolution of 50 rpm and a rotation of 4500 rpm for 90 minutes. Sampling is started to measure the viscosity and solid content, and the guide tube stirring tank is rinsed with NMP to obtain the regeneration liquid. The regeneration liquid is used to adjust the viscosity so that the viscosity is controlled at 5000-10000 cps. During the viscosity adjustment period, the revolution is 25 rpm and the rotation is 1000 rpm. At this point, a slurry with a solid content of 59% and an initial viscosity of 6300 cps is obtained, and stirring is continued at the end point. After 24 hours, the slurry viscosity increases by 18%.
[0127] The positive electrode slurry obtained in this comparative example was prepared at 380 g / m 2 The double-sided surface density is coated on aluminum foil at 2.6g / cm 3 The compaction density was roller pressed, and the final electrode sheet had a diaphragm resistance of 107mΩ.
[0128] Comparative Example 3 (Pulping formula: LFP:CNT:SP:PVDF=97:1:0.5:1.5)
[0129] This comparative example is based on Example 1, but the proportion of fine particles is adjusted. The specific operation steps are as follows:
[0130] (1) According to the slurry formula, the positive electrode active particles (D50 = 1.5 μm, K90 = 3.0) required for slurry are divided into 97 parts, and the weight is recorded as 97 m. The positive electrode active particles are subjected to particle size classification in a dry inertial classification device. The classification is stopped when the weight of the fine particles obtained after multiple classifications reaches 30 m. The D50 of the fine particles is 0.90 μm and K90 is 2.3.
[0131] (2) Mix all the remaining coarse particles (67 m) collected in step (1) with 0.5 m SP, set the double planetary stirring paddles to revolve at 30 rpm and rotate at 100 rpm, and stop after 10 min; add NMP to 0.5 m SP and let the weight of NMP reach 50 m, then let it stand for 10 min; start kneading and stirring, revolve at 50 rpm and rotate at 0 rpm; when a semi-dry uniform mud effect is achieved (i.e., near the kneading state), the initial slurry B is completed, and the solid content of the slurry reaches 57.4%.
[0132] (3) Weigh 1mCNT and 1.5mPVDF, put them all into the guide tube stirring tank, then add NMP until the solid content is 50%, stop adding, let it stand for 5 minutes for capillary absorption, and then continue to add NMP until the solid content is 30%, start stirring, and the stirring rate is 20rpm. At this stage, add NMP while stirring, and stop adding when the solid content reaches 14.3%. At this time, the conductive glue is obtained. After continuing to stir for 5 minutes, add 30m of fine particles obtained by classification in step (1) from the feed port of the guide tube stirring tank, adjust the speed to 30rpm, and after stirring for 30 minutes, observe the agglomeration through a microscope in real time. When no agglomeration occurs when adjusting multiple fields of view, it means that the initial slurry A is successfully prepared. At this time, the solid content of the slurry reaches 68.4%.
[0133] (4) The prepared initial slurry A is released from the bottom valve of the guide tube stirring tank into the double planetary stirring tank, and stirring is started while adding, with a revolution of 50 rpm and a rotation of 500 rpm. After all the initial slurry A is added, the stirring is changed to a revolution of 50 rpm and a rotation of 3000 rpm for 5 minutes, and then changed to a revolution of 50 rpm and a rotation of 4500 rpm for 90 minutes. Sampling is started to measure the viscosity and solid content, and the guide tube stirring tank is rinsed with NMP to obtain the regeneration liquid. The regeneration liquid is used to adjust the viscosity so that the viscosity is controlled at 5000-10000 cps. During the viscosity adjustment period, the revolution is 25 rpm and the rotation is 1000 rpm. At this point, a slurry with a solid content of 59% and an initial viscosity of 7700 cps is obtained, and stirring is continued at the end point. After 24 hours, the slurry viscosity increases by 8%.
[0134] The positive electrode slurry obtained in this comparative example was prepared at 380 g / m 2 The double-sided surface density is coated on aluminum foil at 2.6g / cm3 The compaction density was roller pressed, and the final electrode sheet had a diaphragm resistance of 68mΩ.
[0135] From the comparison between Example 1 and Comparative Examples 1-3, it can be seen that the early classification of the positive electrode active material and the pre-mixing of the fine particles with the thin strip conductive agent have an important influence on the stability of the obtained positive electrode slurry, which can increase the slurry stability and reduce the film resistance of the electrode prepared therefrom.
[0136] The above embodiments and comparative examples illustrate that the positive electrode slurry prepared by the present invention is uniform and stable and can increase the conductivity of the electrode sheet prepared therefrom and reduce the film resistance.
[0137] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a positive electrode slurry, characterized in that: The raw materials of the positive electrode slurry include positive electrode active material, conductive agent, binder and solvent, wherein the conductive agent includes fibrous and / or tubular conductive agent; The preparation method comprises the following steps: S1: dividing the initial positive electrode active material raw material into fine particles and coarse particles according to the powder particle size, and the D50 of the fine particles is (0.1-0.5)*D50 of the initial positive electrode active material; S2: Mixing a fibrous and / or tubular conductive agent, a binder and an appropriate amount of solvent to obtain a conductive adhesive; S3: mixing the fine particles of positive electrode active material obtained in step S1 with the conductive glue obtained in step S2 to obtain an initial slurry A; S4: stirring the coarse particles of the positive electrode active material obtained in step S1 with an appropriate amount of solvent to achieve a kneading state, thereby obtaining an initial slurry B; S5: Knead and stir the initial slurry A and the initial slurry B, and add a proper amount of solvent to achieve the desired viscosity and solid content, thereby obtaining a positive electrode slurry.
2. The method for preparing the positive electrode slurry according to claim 1, characterized in that: The positive electrode active material comprises at least one of lithium iron phosphate positive electrode material, ternary positive electrode material and lithium manganese iron phosphate, and the mass proportion of the positive electrode active material in the total powder raw material is 90% to 98%; And / or, the fibrous and / or tubular conductive agent is selected from at least one of CNT, VGCF, and MWCNT, and the total mass of the conductive agent accounts for 1% to 8% of the total mass of the powder raw materials; And / or, the binder comprises at least one of PVDF and C-PVDF, and the mass proportion of the binder in the total powder raw materials is 1% to 8%; And / or, the solvent is NMP, the total amount of which is based on the solid content of the slurry, and the solid content of the positive electrode slurry is in the range of 45% to 65%; And / or, the viscosity of the positive electrode slurry is 5000-10000 cps.
3. The method for preparing the positive electrode slurry according to claim 1, characterized in that: The conductive agent also includes a point-shaped conductive agent, and the step S4 is replaced by: dry-mixing the coarse-grained positive electrode active material obtained in step S1 with the point-shaped conductive agent, and adding an appropriate amount of solvent and continuing to stir to achieve a kneading state after sufficient stirring, to obtain an initial slurry B; and / or, K90 of the initial positive electrode active material>1.0, wherein K90=(D90-D10) / D50; And / or, the mass percentage of the fine particles in the initial positive electrode active material is 1-15%.
4. The method for preparing the positive electrode slurry according to claim 3, characterized in that: The point-shaped conductive agent is selected from SP; And / or, the K90 of the fine particles is 60% to 95% of the initial positive electrode active material K90.
5. The method for preparing positive electrode slurry according to claim 1, characterized in that: In the conductive adhesive in step S2, The mass percentage of the fibrous and / or tubular conductive agent in the conductive adhesive is 0.5 to 8%; The mass percentage of the binder in the conductive adhesive is 0.1-2%; The amount of solvent added is based on the solid content of the conductive adhesive, and the solid content of the conductive adhesive is 1-15%.
6. The method for preparing the positive electrode slurry according to claim 5, characterized in that: In the preparation process of the conductive adhesive, the appropriate amount of solvent is added in batches; And / or, the preparation of the conductive adhesive is completed in a double-layer stirring and guide tube mixing tank; And / or, the preparation of the initial slurry A is completed in a double-layer stirring and draft tube mixing tank; And / or, the preparation of the initial slurry B is accomplished by using a double planetary high-speed mixer; And / or, the kneading and stirring in step S5 is performed in a double planetary high-speed mixer.
7. The method for preparing the positive electrode slurry according to claim 6, characterized in that: In the preparation process of the conductive adhesive, the adding of the appropriate amount of solvent in batches specifically includes: after the first batch of solvent is added, the solid content of the mixture obtained is 45-55%, after standing for 2-20 minutes, the second batch of solvent is added, and stirring is started when the solid content of the mixture is 25-35%, and then the remaining solvent is added while stirring until the solid content of the mixture is 1-15%, thereby obtaining a conductive adhesive; And / or, the solid content of the initial slurry A is 10-30%; And / or, in step S3, the stirring speed during the mixing is 20 to 100 rpm; And / or, in the double-layer stirring and guide tube mixing tank, a filter is provided on the flow opening located on the side wall of the guide tube, and the flow opening is used for the mutual flow of the material liquid in the main tank and the material liquid in the guide tube, wherein the guide tube is located in the main tank.
8. The method for preparing positive electrode slurry according to claim 6, characterized in that: The preparation of the initial slurry B specifically includes: mixing the coarse particles with the dot-shaped conductive agent, setting a double planetary stirring paddle to revolve at 20-50 rpm and rotate at 80-150 rpm, stirring for 8-15 minutes and then stopping; then adding an appropriate amount of NMP, standing for 8-15 minutes and then starting kneading and stirring until a kneading state is reached, and the kneading and stirring conditions are: revolving at 40-70 rpm and rotating at 0 rpm; and / or, the solid content of the initial slurry B is 55-75%; And / or, the specific method of step S5 includes: adding the initial slurry A to the initial slurry B in the double planetary mixing tank, stirring while adding, and the stirring conditions are: revolution 40-60rpm, rotation 450-550rpm; after the initial slurry A is completely added, the stirring conditions are changed to revolution 40-60rpm, rotation 2500-3500rpm, and continuous stirring for 4-8min, and then the stirring conditions are adjusted to revolution 40-60rpm, rotation 4000-5000rpm, and continuous stirring for 80-100min, then sampling to measure the viscosity and solid content, and controlling the viscosity at 5000-10000cps by solvent, and the stirring conditions during viscosity adjustment are revolution 20-30rpm, rotation 800-1200rpm.
9. The positive electrode slurry prepared by the method according to any one of claims 1 to 9.
10. A positive electrode sheet, comprising a current collector and a positive electrode active material layer disposed on the surface of the current collector, wherein the positive electrode active material layer is formed by coating the positive electrode slurry prepared by the method according to any one of claims 1 to 9 on the current collector.
Citation Information
Cited By
Preparation and coating method of lithium ion battery pole piece coating slurry
CN120895600A
Low-porosity and low-impedance solid-state battery dry-method positive electrode and preparation method thereof
CN121331761A
Low porosity, low impedance solid state battery dry method cathode and method of making same
CN121331761B
Positive electrode material for lithium-ion battery, and positive electrode and lithium-ion battery comprising same
WO2026179577A1